Displacement speed statistics in an open turbulent jet spray flame. (15th February 2021) - Malkeson, S.P.; Ahmed, U.; Turquand d'Auzay, C.; Pillai, A.L.; Chakraborty, N.; Kurose, Ryoichi
Graphical abstract: Abstract: In this study, a three-dimensional Direct Numerical Simulation of an open turbulent jet spray flame has been used to investigate the statistical behaviour of displacement speed S d and its components to provide physical explanations for the observed behaviours at different axial locations downstream of the jet exit. The open turbulent jet spray flame exhibits fuel-lean conditions close to the jet exit but fuel-rich conditions have been observed further downstream due to the evaporation of fuel droplets. For the axial locations considered, combustion takes place under low Damköhler number conditions. The displacement speed of reaction progress variable isosurfaces shows qualitatively similar behaviour for all axial locations considered – predominantly positive across the major part of the flame but with small, potentially negative, values towards the burned-gas-side. The components of displacement speed arising from chemical reaction rate and flame normal molecular diffusion remain leading order contributors and the competition between these determines the mean behaviour of displacement speed. These observations are consistent with studies of turbulent spray flames in canonical configurations and low Damköhler number turbulent premixed and stratified flames. This suggests that flow geometry in the absence of mean curvature might not be important in determining the mean behaviour of displacement speed and its components. Therefore, the modelling methodologies employed for turbulent stratified flames can potentially be extended for turbulent spray flames. However, the modelling methodologies, which implicitly assume equality between the surface-weighted values of density-weighted displacement speed and local laminar burning velocity, might be rendered invalid for turbulent spray flames.